A Unique SUMO-Interacting Motif of Trx2 Is Critical for Its Mitochondrial Presequence Processing and Anti-oxidant Activity - Chen, Chaofei; Wang, Kang; Zhang, Haifeng; Zhou, Huanjiao Jenny; Chen, Yuxin; Min, Wang (Frontiers in Physiology, 2019)
Objective: Mitochondrial thioredoxin 2 (Trx2) is a vital mitochondrial redox protein that mediates normal protein thiol reduction and provides electrons to peroxiredoxin 3 (Prx3) to scavenge H2O2 in mitochondria. It has been widely reported that Trx2 deletion in cells or mice generates massive reactive oxygen species (ROS) which have been implicated in many pathological processes. On the contrary, how ROS regulate Trx2 expression and activity remains to be elucidated. Approach and Results: Here we show that excess ROS induce endothelial cell senescence concomitant with an attenuation of Trx2 processing in which Trx2 presequence (i.e., mitochondrial targeting signal peptide (MTS)) is cleaved to generate a mature form. Mutation analyses indicate that Trx2 processing is mediated by mitochondrial processing peptidase (MPP) and mitochondrial intermediate peptidase (MIP)-recognition sites within the MTS. Interestingly, a mutation at a SUMO- interacting motif (SIM), but not the catalytic sites within the mature Trx2 protein, completely blocks Trx2 processing with no effect on Trx2 mitochondrial targeting. Consistently, chemical inhibition of protein SUMOylation attenuates, while SUMOylation agonist promotes, Trx2 processing. Moreover, we identify the MPP subunit is a SUMOylated protein that potentially mediates Trx2-binding and cleavage. Furthermore, the unprocessed form of Trx2-SIM is unable to protect cells from both ROS generation and oxidative stress-induced cellular senescence. Conclusion: Our study reveals that a unique SUMO-interacting motif of Trx2 is critical for its mitochondrial processing and subsequent anti-oxidant/antisenescence activities.